KONTROVERSI PEREMPUAN MENJADI IMAM SALAT DI KALANGAN FUKAHA - Ali Trigiyatno (Jurnal Hukum Islam, 2014)
One of the women issues that has been struggled for by women is equivalence in every sector includes the equivalence in religion sector: prayer. In this case,somewomen—one of them is Amina Wadud—started to introduce and even demonstrated her opinion that women can be theimam of prayers at the open place with various jama’ah from men to women, and it is sah. Although this opinion was not new, because far before that, al-Muzani, Abu Saur and In Jarir at-Tabari had made a fatwato permit that. But the fuqaha tended to forbid and oppose it. This article tried to describe that khilafiyah, complete with the ulama and the arguments as the bases.